Galumna capensis dissimilis Engelbrecht, 1969, a junior synonym of Galumna lawrencei Jacot, 1940 (Acari, Oribatida, Galumnidae), with remarks on type material - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A. (Zootaxa, 2020)
The morphology of adult instars of two South African oribatid mites Galumna lawrencei Jacot, 1940 and Galumna capensis dissimilis Engelbrecht, 1969, is analyzed, resulting in the following new taxonomic proposal: G. lawrencei Jacot, 1940 (=G. capensis dissimilis Engelbrecht, 1969 syn. nov.). Comparison was based on the lectotype and paralectotypes (for G. lawrencei) and on the holotype and paratypes (for G. capensis dissimilis). Comments are made on the type material.